PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAH DAN PENERAPAN GOOD GOVERNANCE AND CLEAN GOVERNMENT TERHADAP KUALITAS LAPORAN KEUANGAN (Studi Kasus pada Pemerintah Kabupaten Rembang) - Rosa Maisyaroh; Haryanto Haryanto (Diponegoro Journal of Accounting, 2023)
The samples in this study were heads of SKPD offices/agencies, secretaries of SKPD offices/agencies, and employees in the financial sector/treasurers at agencies/SKPDs throughout Rembang Regency. The sample is based on purposive sampling method. The samples obtained were 117 respondents. The research method used is hypothesis testing research using the SPSS 27 software test tools. The results show that the statement of government accounting standards has a significant effect on the quality of financial reports. This is also the same as the second variable that Good Governance and Clean Government also affects the quality of financial reports to obtain a positive and significant value. As well as the application of government accounting standards, Good Governance and Clean Government affect the quality of financial reports to obtain a positive and significant value.